A long range restriction map of the distal human X chromosome short arm around the steroid sulfatase locus. - Li, X M (1990)
The distal short arm of the human X chromosome is of interest because it contains genes which escape X chromosome inactivation and because it is subject to frequent deletions in human patients. The steroid sulfatase gene has been particularly well studied as an example of a gene which escapes X inactivation and which is included in a number of these deletion events. For these reasons a physical map of the region around the STS gene would be of interest. We have constructed a rare cutting enzyme map of this area and have determined the position of several nearby markers with respect to STS. We have also oriented the 5' and 3' ends of the STS gene on this map and have determined the centromeric and telomeric portions of the region. Finally, we have shown that this map can be used to locate deletion breakpoints in STS deficient patients.